30 anos de geologia de engenharia na UFRJ: visões do passado e do futuro - Barroso, Josué Alves; Cabral, Sérgio (Anuário do Instituto de Geociências, 1997)
When the fifth specialized school of geologists was created in Brazil, in the Rio de Janeiro City (1958), the Engineering Geology was one of the earliest matters included as an applied discipline of undergraduate geology curriculum. Some years late it became the main subject to begin the Departamento de Geologia UFRJ posgraduation course. Nowadays, celebrating its thirtieth anniversary, an historical review is made to settle its importance to students with geotcchnical interests, its succss on professional improvement and the whole of its scientific production.